Parâmetros temporais em português brasileiro: investigação das estruturas lexicogramaticais orientada para os estudos linguísticos da tradução - Arthur de Melo Sá (2020)
Drawing on systemic functional linguistics (HALLIDAY; MATTHIESSEN, 1999, 2014) and being affiliated to the systemic functional approaches to translation (PAGANO; VASCONCELLOS, 2005; MATTHIESSEN, 2001; TEICH, 2001, 2003), this thesis investigates the meaning potential of the language contact between Brazilian Portuguese and English with a focus on the basic temporal parameters theorized by Halliday and Matthiessen (1999) and their lexicogrammatical realizations. This research follows Halliday and Matthiessen (1999) guiding principles for the description of semantic phenomena and the four basic parameters for studying the construal of temporal experience: location, perspective, staging and profile. This thesis takes into account previous description proposals (CÂMARA JR., 1999; CUNHA; CINTRA, 2017; CEGALLA, 2008; PERINI, 2005; TRAVAGLIA, 1991, 2014; CASTILHO, 1967, 2010; BECHARA, 2009; NEVES, 2000; BAGNO, 2012), which address the construal of experience of time from the syntagmatic axis, focusing almost exclusively on the lexicogramatical word rank. In view of the need pointed out in the systemic functional theory for a description to treat structural relations as derived from paradigmatic ones (HALLIDAY, 1966, 2002, 2003a; CAFFAREL; MARTIN; MATTHIESSEN, 2004a, p. 23), this thesis describes how lexicogramatical structures realize different possibilities of semantic choices for construing the experience of time. This thesis also investigates the experience of time in the language contact between Brazilian Portuguese and English, with a focus on the potential pole of the instantiation cline. Previous research addresses the experience of time from other branches of translation studies (e.g., APPELO, 1986, 1994; OLSEN et al., 2000) and other theoretical frameworks (RODRIGUES, 2000; RAMALHO, 2004). And even though this thesis and Braga (2016) share a common approach and theoretical framework, Braga (2016) does not focus her analysis on the description of the meaning potential of the experience of time. This thesis, with a focus on the system pole, allows for understanding the experience of time as a multilingual meaning potential, with intersections and divergences in the lexicogrammatical system networks construing experience of time in Brazilian Portuguese and English. Thus, this research addresses Figueredo (2015a) proposal for modeling the multilingual environment. Figueredo (2015a) proposes that, in order to understand the production of meaning in the multilingual space, it is necessary to identify intersections and disjunctions between systems networks of languages in contact. This thesis aims at contributing (i) to the systemic-functional description of Brazilian Portuguese and (ii) to systemic-functional translation studies. To this end, the following specific objectives are defined: (1) to map the realization of experience of time according to the parameters of location, perspective, stage and profile in Brazilian Portuguese in each lexicogramatical unit: (a) clause, in relation to the structures that realize the systems of TRANSITIVITY, MOOD and THEME, (b) group, in relation to the structures that realize the systems of SECONDARY TENSE, AGENTIVITY, VERBAL ASPECT, FINITENESS and MODALITY, and (c) word, in relation to the structures that realize the systems of INTERPERSONAL ORIENTATION and EXPERIENCE MODIFICATION; (2) to compare the structures of Brazilian Portuguese and English that realize the experience of time according to the parameters of location, perspective, stage and profile in the units of clause, group and word; (3) to identify similarities and differences in the systems networks of clause, group and word that organize the structures that realize the temporal experience in Brazilian Portuguese and English. In this study, a sample of texts originally written in Brazilian Portuguese was selected from the Klapt! corpus (NUNES, 2010, 2014; FERREGUETTI, 2014), arranged in eight categories (Research Article, Political Speech, Popular Science, Fiction, Instructions Manual, Tourism Leaflet, Review and Educational Website). This sample composed the corpus of analysis, with approximately 480 sentences – or 10776 words. This corpus was segmented into semantic figures, clauses, verbal groups and verbs and annotated using electronic spreadsheets. Corpus analysis revealed the structural patterns that construe the temporal parameters in the clause, the group and the word according to each metafunction (ideational, interpersonal and textual). Results consist of a mapping of the structures that realize systems of the clause (MOOD, TRANSITIVITY and THEME), the verbal group (FINITENESS, MODALITY, SECONDARY TENSE, EVENT TYPE, AGENTIVITY and VERBAL ASPECT) and the verb (INTERPERSONAL ORIENTATION and EXPERIENCE MODIFICATION) and demonstrate how each temporal parameter (location, perspective, staging and profile) is construed. As regards the contributions to linguistics, this thesis (i) validates theoretical concepts and description methods developed in systemic functional linguistics; (ii) presents a new approach to the description of time in Brazilian Portuguese and continues the systemic description of this language, focusing on the construal of the temporal parameters; and (iii) provides useful information for other areas of the multilingual studies (MATTHIESSEN; TERUYA; WU, 2008), such as typology and translation studies, by comparing the systems, structures and functions that realize the experience of time in Brazilian Portuguese with English, French, Russian, Greek, Chinese, Quechua, etc.